Drug- and Alcohol-Associated Deaths in U.S. Jails. (April 2020) - Fiscella, Kevin; Noonan, Margaret; Leonard, Susan H.; Farah, Subrina; Sanders, Mechelle; Wakeman, Sarah E.; Savolainen, Jukka
Drugs and alcohol are the third leading cause of death in U.S. jails. We analyzed 2000 to 2013 national jail mortality data by coding text data. We identified 1, 442 deaths associated with drugs and alcohol. Drug-associated deaths were more than double alcohol-associated deaths during 2009 to 2013 when drug type was available for drug-associated mortality. Only 18% of deaths within 7 days of arrest for alcohol intoxication were officially coded as involving drugs/alcohol intoxication. Among the 103 deaths associated with substance withdrawal, 66 involved alcohol, 21 involved drugs (primarily opioids), and 16 could not be determined. Drugs and alcohol likely contribute to more deaths in jails than has been recognized due to how deaths are coded. Alcohol and opioid withdrawal represent a small but underappreciated contributor to jail deaths.